DEVELOPING AN INTEGRAL SUSTAINABILITY PATTERN LANGUAGE. - Winton, Tim (Journal of Integral Theory & Practice)
This article introduces an experimental typology and its application to the development of Integral Sustainability. The typology, PatternDynamics™, is derived from observations and experiences of natural and social systems and the study of systems disciplines. It is composed of a set of graphic symbols representing natural organizing principles, or recurrent dynamic patterns of structure and relationships, important for sustaining ecological and economic health in the Lower- Right quadrant of the AQAL model. As a typology functioning within the Integral framework, PatternDynamics™ contributes to an Integral semiotics by exploring new methods of enhancing communication and understanding of the principles of sustainability. In this way, a typology functions as a language of natural patterns--a "sustainability pattern language"--facilitating the creation of meaning and mutual understanding about Lower-Right sustainability within the Lower-Left quadrant. Climate change is discussed as an example of how Integral Theory and PatternDynamics™ may be used to explore sustainability topics more comprehensively. Additionally, this article explores types and their role in the Integral framework, the origins of contemporary pattern languages, and the understanding, development, and use of PatternDynamics™ as an Integral Sustainability communication tool.